2017
DOI: 10.1259/bjr.20170064
|View full text |Cite
|
Sign up to set email alerts
|

Intercountry analysis of breast density classification using visual grading

Abstract: Purpose: Disagreement in mammographic breast density (MBD) assessment can impact breast cancer risk stratification, choices of further breast cancer screening intervals and pathways. This study examines whether inter-country MBD expectations and assessment approaches are associated with differences in MBD assessment. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
6
1
Order By: Relevance
“…This could be due to variable perception on the part of radiologists and can be improved by training based on standards and reference images [3]. However, this study's agreement levels are higher than previously reported studies which did not incorporate observer training, either oral or Atlas BI-RADS instruction [6,26,[42][43][44] but similar to studies that included clear BI-RADS instructions for participants [7]. This could be due to enrollment bias, as at the time of the research activity, both radiology cohorts were involved in specialized mammography-focussed activity, and breast density was considered an important topical issue.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…This could be due to variable perception on the part of radiologists and can be improved by training based on standards and reference images [3]. However, this study's agreement levels are higher than previously reported studies which did not incorporate observer training, either oral or Atlas BI-RADS instruction [6,26,[42][43][44] but similar to studies that included clear BI-RADS instructions for participants [7]. This could be due to enrollment bias, as at the time of the research activity, both radiology cohorts were involved in specialized mammography-focussed activity, and breast density was considered an important topical issue.…”
Section: Discussioncontrasting
confidence: 55%
“…Many studies have been undertaken to test interobserver variability in assessing breast density. They vary in the number of radiologists included, the methodology used, and the results [6,25,26,[42][43][44]. However, this study sought to explore the establishment of the variation in two countries, the USA and UK, using a greater number of expert radiologists reviewing a larger number of images compared to previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that radiographers could do breast density assessment, but this has been shown to result in even less agreement (kappa 0.69 versus 0.62) (184 (197). Still, even when using their native scales, readers from U.K. had worse agreement compared to readers from U.S., with even lower agreement among Australian radiologists (198). This indicates that BI-RADS density has relatively higher agreement compared to alternative subjective scales.…”
Section: Moving From Subjective To Objective Breast Density Assessmentmentioning
confidence: 99%